DEVELOPING A GUIDE MODULE FOR THE PREPARATION OF LEARNING OUTCOME TEST INSTRUMENT BASED ON HIGH ORDER THINKING SKILLS ON HISTORY SUBJECT - Bunari; Asyrul Fikri; Yanuar Al Fiqri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to create a guide module for learning outcome test based on High Order Thinking Skill (HOTS) in lectures at the Departement of History Education at Universitas Riau in Penilaian Pembelajaran Sejarah course. The research method used in this research was research and development adopting 4-D (Four-D) development model. In this research, the development focused on the creation of a guide module for the preparation of learning outcomes instruments based on High Order Thinking Skills. The validation result from the material expert was 3.8 (very feasible) while the validation result from the language expert was 3.6 (very feasible), and the results of the module trial for students was 96.22 (very positive). Thus, the guide module was suitable to be utilized as teaching materials in Penilaian pembelajaran Sejarah course at the Deaprtment of History Education, Universitas Riau.